Effects of carbon dioxide on cell growth and propionic acid production from glycerol and glucose by Propionibacterium acidipropionici. (January 2015) - Zhang, An; Sun, Jianxin; Wang, Zhongqiang; Yang, Shang-Tian; Zhou, Haiying
Highlights: CO2 enhanced propionic acid production in glycerol fermentation. CO2 enhanced cell growth in glycerol fermentation. CO2 had no significant effect in glucose fermentation. A stoichiometric metabolic model was used to illustrate carbon flux distribution. Abstract: The effects of CO2 on propionic acid production and cell growth in glycerol or glucose fermentation were investigated in this study. In glycerol fermentation, the volumetric productivity of propionic acid with CO2 supplementation reached 2.94 g/L/day, compared to 1.56 g/L/day without CO2 . The cell growth using glycerol was also significantly enhanced with CO2 . In addition, the yield and productivity of succinate, the main intermediate in Wood–Werkman cycle, increased 81% and 280%, respectively; consistent with the increased activities of pyruvate carboxylase and propionyl CoA transferase, two key enzymes in the Wood–Werkman cycle. However, in glucose fermentation CO2 had minimal effect on propionic acid production and cell growth. The carbon flux distributions using glycerol or glucose were also analyzed using a stoichiometric metabolic model. The calculated maintenance coefficient ( m ATP ) increased 100%, which may explain the increase in the productivity of propionic acid in glycerol fermentation with CO2 supplement.